Food Allergy: Present and Future Management - Ananth Thyagarajan, MD; A. Wesley Burks, MD (World Allergy Organization Journal, 2009)
Food allergy poses a significant burden on patients, families, health care providers, and the medical system. The increased prevalence of food allergy has brought about investigation as to its cause and new treatments. Currently, the only treatment available is to avoid the food and symptomatically treat any reactions. There are multiple clinical and murine models of food allergy treatment that use allergen specific and nonspecific pathways. Allergen specific treatments use mucosal antigen exposure as a method of inducing desensitization and tolerance. Allergen nonspecific methods act via a more global TH2 suppressive mechanism and may be useful for those patients with multiple food allergies. Keywords: food hypersensitivity, treatment, immunotherapy